Association of Chlamydia trachomatis and Neisseria gonorrhoeae with female infertility: a systematic review and meta-analysis - Araz Majnooni; Saeed Amel Jamedar; Amir Azimian; Kiarash Ghazvini (Faculty of Medicine, Universitas Trisakti, 2022)
BackgroundChlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) are commonly diagnosed sexually transmitted infections that have been associated with serious reproductive health outcomes for women. The association of CT and NG infection with female fertility is not completely established yet. This review aimed to determine the association of CT and NG with female infertility. MethodsThis systematic review and meta-analysis was conducted according to the PRISMA statement. We searched a range of electronic databases, including PubMed, Web of Science, Embase, and Scopus, from Sept 25, 2017 until February 1, 2021. From the 851 studies screened, 552 that failed to meet our eligibility criteria were excluded. Subsequently, we removed 290 studies for not having a possible correlation of CT and NG infections with female infertility. Nine studies comprising 1827 infertile patients met our inclusion criteria. Two investigators independently extracted a range of data. All analyses were performed using STATA (version 13.1, Stata Corp, College Station, TX, USA). ResultsCT infection potentiates female infertility, as 76.47% of the included studies found a positive correlation between them. However, due to the limited number of reported data, we were not able to compare NG infection prevalence in fertile and non-fertile patients. Overall prevalences of CT and NG infections among infertile patients were 12 % and 3%, respectively, while CT infection prevalence among the fertile group was 7%. Conclusion The prevalences of CT and NG infections were high in infertile women. Screening and treatment of C. trachomatis and gonococcal infections during infertility treatment might increase the pregnancy rate.